Implementasi Ecobox Smart Dryer Berbasis IoT untuk Produksi Tepung Labu Kuning sebagai Pangan Alternatif - Felix Andreas Sutanto; Dewi Handayani Untari Ningsih; Mohammad Riza Radyanto; Saefurrohman Saefurrohman (GUYUB: Journal of Community Engagement, 2025)
Bulungcangkring Village in Jekulo District, Kudus Regency, has strong agricultural potential, with most residents working as farmers. Some have begun cultivating non-rice commodities such as pumpkin and purple sweet potato, which offer opportunities for value-added processing and increased income. KUB Elbina, a 20-member local enterprise group, focuses on processing these agricultural products, especially pumpkin flour. However, the group faces technological limitations, particularly in post-harvest drying, which is still done through open sun drying. This method requires ±24 hours, yields only ~70%, depends heavily on weather, and poses contamination risks from dust, insects, and microorganisms, resulting in inconsistent product quality, including non-uniform flour color. This community service program implements an IoT-based Ecobox Smart Dryer as an appropriate technology to improve processing efficiency and product quality using a Participatory Action Research (PAR) approach. Activities include problem identification, equipment installation, training, production assistance, and evaluation. The results show significant improvements: drying time reduced to ±8 hours, yield increased to ~90%, moisture content stabilized at ≤10%, and flour color became more uniform. The program outputs include a fully functioning Smart Dryer, enhanced production capacity, improved product quality, and strengthened operator skills.